(untitled) (Psychology Travelogs, 2025)
The article is devoted to the study of the impact of creating mandalas for psychological correction (reduction) of the level of distress of adolescents. The symbolic content of the mandala and its impact on the human psyche are analyzed. It is shown how creating mandalas helps adolescents express their emotions and improve their general mental state. A number of recommendations are proposed for the further implementation of techniques for creating mandalas in psychological practice. Two techniques of creating mandalas are compared: drawing on paper and weaving from threads. The study showed that different methods of creating mandalas have a slightly different effect on the level of distress of adolescents. Comparing the creation of mandalas on paper and from threads, we found that both approaches effectively reduce the level of distress, but creating a mandala from threads has a more pronounced effect. It was found that adolescents who participated in the creation of mandalas from threads demonstrated a significantly more stable emotional state compared to those who worked with mandalas on paper. Accordingly, weaving mandalas from threads is better suited for working with adolescents who are in a state of severe stress or emotional exhaustion. Thus, comparison of the results of the empirical study before and after creating mandalas revealed that both drawing and weaving mandalas reduce the distress of adolescents, while the effect of weaving mandalas is more pronounced and stable. So, the creation of mandalas from threads is a promising tool for working with adolescents, which not only helps reduce emotional tension, but also provides a deeper stabilization of the emotional state, forming stable self-regulation and relaxation skills. Prospects for further research: a more detailed study of the impact of different techniques for creating mandalas for psychocorrectional work, especially of creating mandalas from threads on emotional states.